Genetic analysis of yield and other characters in two populations of maize - MARKER, SHAILESH (The Indian Journal of Agricultural Sciences, 2011)
Genetic studies were conducted on progenies developed in 2 maize populations, namely 'Mahikanchan' and 'Mahidhawal' using North Carolina Design- 1. Significant differences among males in sets as compared to females in males in sets for all the traits in the study indicated, substantial co~ltributiono f plants chosen as males towards the variation anlong progenies. Additive genetic variance was more pronounced than dominance variance for all the traits studied, indicating the importance of additive gene effects. No dominance to partial dominance was observed for grain yield , ear length, ear diameter, 100-grain weight, kernel rows per ear and days to 50%) silking. Narrow sense heritability was moderate for grain yield and full sib family selection was found superior to the mass selection for all the traits studied in both the populations.